2020
DOI: 10.3390/insects11030159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-Lethal High-Temperature Stress on Bradysia odoriphaga (Diptera: Sciaridae) Larval Development and Offspring

Abstract: Throughout China, the dipteran pest Bradysia odoriphaga significantly reduces Chinese chive production; therefore, identifying conditions that influence its growth and development is crucial for developing ecological regulation strategies. In this study, different non-lethal high temperatures and treatment durations were used to stress the third-instar larvae of B. odoriphaga, and the effects of this treatment on their growth and offspring were recorded and analyzed. The results showed that the average larval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This study demonstrates that the rate of pupal emergence gradually decreased as temperature and treatment time increased after pupal-stage exposure to high temperature. A significant reduction in emergence rate was observed after pupal-stage exposure to 44 °C for 6 h, which is consistent with a similar study [ 35 ]. The pupae of Grapholita molesta were exposed to high temperatures, which increased their longevity and reduced fecundity [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates that the rate of pupal emergence gradually decreased as temperature and treatment time increased after pupal-stage exposure to high temperature. A significant reduction in emergence rate was observed after pupal-stage exposure to 44 °C for 6 h, which is consistent with a similar study [ 35 ]. The pupae of Grapholita molesta were exposed to high temperatures, which increased their longevity and reduced fecundity [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…13 However, once the temperature exceeds their tolerance limits, it will lead to short (e.g., decreased survival rate or immediate death) and long-term adverse effects (i.e., potential carry-over effects on subsequent development stages and fecundity). [14][15][16][17] Most insect species suffer from temperature fluctuations in their dwelling environment throughout their ontogeny, which affects physiological processes and ecological functions. It is known that different developmental stages of insects have different thermal sensitivities, so high temperatures experienced in early ontogeny can affect biological characteristics and heat tolerance capacities in later development stages or the next generation.…”
Section: Introductionmentioning
confidence: 99%
“…In general, insects possess certain physiological self‐regulation functions in order to tolerate temperature changes 13 . However, once the temperature exceeds their tolerance limits, it will lead to short (e.g., decreased survival rate or immediate death) and long‐term adverse effects (i.e., potential carry‐over effects on subsequent development stages and fecundity) 14–17 …”
Section: Introductionmentioning
confidence: 99%
“…The responses of B. odoriphaga and B. impatiens to high temperatures have been reported (Gou, Guo, Wang, et al, 2020;Zhu et al, 2018). But previous studies focused mostly on lethal and sublethal short-term heat shocks and lacked the whole generation observations under constant high temperature exposure (Luo et al, 2017;Shi et al, 2020;Zhu et al, 2017Zhu et al, , 2018. Cheng et al reported negative effects of high temperatures (31, 33, 35 and 37°C) and exposure times (from 0 min to 120 min) on the survival, fecundity and offspring development of B. odoriphaga (Cheng et al, 2017).…”
Section: Bradysia Odoriphagamentioning
confidence: 99%